SISTEM INFORMASI PENCATATAN DATA INVENTARIS BERBASIS MULTIUSER (STUDI KASUS PADA RSUD AMBARAWA - Tery Aditya Putra (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2021)
The Regional General Hospital (RSUD) Ambarawa is one of the Public Service Agency Region(BLUD) belongs to Semarang Regency which is engaged in public health services. Ambarawa Hospital islocated at Jalan Kartini No. 101 Ambarawa. During this inventory data processing pengolahan At theRegional General Hospital (RSUD) Ambarawa it is still processed manually, some problems what oftenarises is not knowing the value of depreciation of goods each month, has not applied database system andlow inventory data security system.The author uses 3 research methods for data collection in this study, namely observation, interviewsand literature study. The observation method used by the author is by carry out direct practice on theproblems that occur. Interviews were conducted by the author on the employees concerned, while in theliterature study the author looks for related literature with research and used as a theoretical basis. From theanalysis and research results, it can be seen that the solution to the above problems is by create an InventoryData Recording Information System that uses a programming languageMicrosoft Visual Basic 6.0 and Microsoft SQL Server 2000 database processing system. Theprocedure will be made consisting of 5 main parts, namely the inventory item data collection, room datacollection, transactions for placement of inventory items, transactions for mutation of inventory items anddepreciation of the line method straight. This system is expected to increase the effectiveness of inventorydata processing in hospitalsRegional General Hospital (RSUD) Ambarawa.